2014
DOI: 10.1149/2.0091502jss
|View full text |Cite
|
Sign up to set email alerts
|

Ceria-Based Slurries for Non-Prestonian Removal of Silicon Dioxide Films

Abstract: A slurry with a non-Prestonian dependence on the polishing pressure can help in minimizing dishing and erosion during shallow trench isolation chemical mechanical planarization. Here, we show that ceria-based slurries containing diallyldimethylammonium chloride (DADMAC) yield a non-Prestonian blanket film polish rate with a low threshold pressure (1-2 psi) when polishing plasma-enhanced chemical vapor (PECVD) tetraethylorthosilicate (TEOS) deposited oxide as well as thermal oxide films. The polishing mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 51 publications
2
20
0
Order By: Relevance
“…The measured force-distance curves in DI water at pH 4 with and without DADMAC additive are correlated with the non-Prestionian oxide removal rate behavior reported in Ref. 7 along with the coefficient of friction (COF) values obtained during CMP.…”
Section: -11supporting
confidence: 70%
See 3 more Smart Citations
“…The measured force-distance curves in DI water at pH 4 with and without DADMAC additive are correlated with the non-Prestionian oxide removal rate behavior reported in Ref. 7 along with the coefficient of friction (COF) values obtained during CMP.…”
Section: -11supporting
confidence: 70%
“…The results obtained were used to explain the observed non-Prestonian oxide removal reported earlier in Ref. 7. The AFM force measurements showed that there is a repulsive interaction between the IC1000 pad and oxide film surface at pH 4 with and without DADMAC additive indicating that the interaction of these surfaces has minimum effect in oxide removal.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Therefore, CeO 2 particles can be found in wastewaters from CMP polishing operations. 23 Six different waste samples were collected from a typical CMP process as follows. CGS/SiN and CGS/SiO 2 : 0.1 wt % ceria slurry with glycine and nicotinic acid used for silicon nitride (SiN) and silicon oxide (SiO 2 ) wafers polishing with measured pH values of 4.3 and 4.45, respectively.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%